Economic and social impacts of armed conflicts: Assessing the effects of military operations on development - Petrukha, Nina; Andrieiev, Andrii; Mukhin, Oleksii; Morozov, Oleh; Stebletskiy, Igor (Edelweiss Applied Science and Technology, 2024)
The paper highlights the impact of military conflicts on society’s socio-economic development. A review of scientific publications on the subject is carried out. The impact of the Russia-Ukraine military conflict on the socio-economic development of Ukraine is considered based on regression analysis. The main consequences of military operations in Ukraine are outlined. The approaches of the leading international organisations to accounting and auditing the consequences of conflicts and wars are determined. Examples are given, and the main aspects of accounting for losses caused by military conflict in different countries are compared. The study aims to comprehensively analyse and assess the impact of military conflicts on economic development and social aspects of society. Regression analysis methods were used to determine the relationship between military conflicts and economic indicators such as GDP, inflation, unemployment, public debt, defence spending, scientific data analysis, synthesis and comparison, and geospatial and comparative analysis, which helped to assess the direct and indirect effects of conflicts on economic development and the social sphere in Ukraine. The article analyses the social consequences of the military conflict in Ukraine in 2014–2024. An empirical analysis of economic losses from military conflicts is carried out. The need for an integrated approach to assessing and overcoming the consequences of wars and conflicts and coordination between government organisations, local communities and international partners to achieve sustainable development and restore the country’s socio-economic situation is established.